Collaboration Strategy of BRI in Optimizing Integrated Ecosystem for Intermediation Effectiveness - Sanjoyo, Eli; Adhisuryo, Raghutama Haryo; Harto, Puji; Hararja, Surya (Economic and Business Horizon, 2025)
This study aims to analyze the the collaboration strategy of PT bank rakyat Indonesia (Persero) Tbk in optimizing the integrated business ecosystem to support the effectiveness of the Intermediation Function. The focus of this research is on the wholesale segments. This research uses a mixed methods approach, with quantitative data processing based on BRI's financial statements for the 2020-2024 period, and qualitative analysis through documentation studies and content analysis from official company sources. The results showed that the collaboration strategy in the Wholesale segments can increase the effectiveness of the intermediary function which is marked by an increase in the LDR ratio, CASA and a significant growth in third party funds. Surprising results are also seen in the indicators of the integrated system itself where each component such as trade finance, bank guarantees and Lola Cash Management volume also experienced a significant increase from year to year. The implications of these findings emphasize the importance of expanding partner networks, innovating digital services, and synergizing between actors in the ecosystem as key strategies in improving bank competitiveness and supporting intermediation functions in a sustainable manner